Nafcillin Treatment of Staphylococcus aureus Meningitis - Ruiz, Daniel E. (1976)
Serial serum and cerebrospinal fluid nafcillin concentrations were determined in a patient successfully treated with nafcillin (200 mg/kg per day) for Staphylococcus aureus bacteremia and meningitis. Nafcillin and methicillin cerebrospinal fluid concentrations were compared.